Węgierskie nocne rodaków rozmowy. Wokół antologii Gwiazda przewodnia. Węgierski październik 1956 w rodzimej poezji i prozie - Ratajczak, Wiesław (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
Jerzy Snopek’s anthology Gwiazda przewodnia. Węgierski październik 1956 w rodzimej poezji i prozie (Guiding star: Hungarian October 1956 in Polish poetry and prose) contains outstanding relations and reflections on the drammatic moment in history. The authors of works quoted in the collection were interested in, among other things, the combination of the personal and the collective, existential and historical, palpable and metaphysical.